The Use of Demonstration Methods to Improve The Mastery of Hajj Material for Students Class VIII MTs Al Wahid Pape Islamic Boarding School - Syarifuddin (IAIN Parepare, 2023)
This study discusses the Analysis of the Use of Demonstration Methods to Increase Mastery of Hajj Materials in the Fiqih Subject for Grade VIII MTs Al Wahid Pape Islamic Boarding School, Sidrap Regency. This type of research is Classroom Action Research or Classroom Action Research (PTK). The results of this study indicate, (1) Students' understanding of Hajj material in Fiqh learning, can be seen in the learning process in cycle I, namely obtaining an average value obtained of 6.57. (2) Efforts to increase students' understanding of pilgrimage can be reached using the demonstration method. Cycle I at the beginning of the lesson begins with using audio-visual media, in cycle II using demonstration methods. (3) Increased understanding of pilgrimage by using the demonstration method, namely the acquisition of an average value in which each cycle has increased. Cycle I the average value obtained was 6.57, in cycle II it increased, namely 7.57, and experienced another increase in cycle III, namely obtaining an average value of 8.33.